2012
DOI: 10.1111/j.1464-410x.2012.10993.x
|View full text |Cite
|
Sign up to set email alerts
|

Marital status: a gender‐independent risk factor for poorer survival after radical cystectomy

Abstract: 3 0 1What ' s known on the subject? and What does the study add? Married individuals have lower morbidity and mortality rates for all major causes of death. Cancer-specifi c survival is better in married patients with testis cancer, prostate cancer, breast cancer, cervical cancer, as well as head and neck cancers.We have found the effect of marital status on outcomes after radical cystectomy to be variable, depending on gender and the outcome addressed. Being married is predictive of lower all-cause mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 23 publications
9
37
0
1
Order By: Relevance
“…The stronger survival benefit of marriage among men confirms prior research 1,2,23,24 and may provide important clues into underlying mechanisms. Men and women appear to benefit differentially from marriage, 2528 with women benefitting more financially and men benefitting more socially.…”
Section: Discussionsupporting
confidence: 79%
“…The stronger survival benefit of marriage among men confirms prior research 1,2,23,24 and may provide important clues into underlying mechanisms. Men and women appear to benefit differentially from marriage, 2528 with women benefitting more financially and men benefitting more socially.…”
Section: Discussionsupporting
confidence: 79%
“…The consistent protective effect of marriage seen on uterine cancer survival after adjustment is on par with marriage benefits proposed in numerous other studies [1][2][3][4][5]. More importantly this study identifies widows as having an elevated risk of death from uterine cancer and the poor outcome of widows accounted for most of the survival advantage ascribed to marriage.…”
Section: Discussionsupporting
confidence: 65%
“…The observation that married patients had a uterine cancer survival advantage relative to those who were not married is consistent with the survival benefit of marriage reported in other cancer sites [1][2][3][4][5]. Multivariate Cox modeling and Kaplan-Meier method were used to extend the prior studies by comparing uterine cancer survival in singles vs. married women vs. widows vs. others.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Marriage may have a protective effect on prognosis of cancer patients. Studies indicated that unmarried patients were at higher risk of presentation with metastatic cancer, undertreatment, and shorter survival in various cancer types 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. Mixed 13, 14, 15, 16 or no significant 17, 18, 19 associations between marital status and cancer survival were reported as well.…”
Section: Introductionmentioning
confidence: 99%